Human amygdala stimulation effects on emotion physiology and emotional experience. (August 2020) - Inman, Cory S.; Bijanki, Kelly R.; Bass, David I.; Gross, Robert E.; Hamann, Stephan; Willie, Jon T.
Abstract: The amygdala is a key structure mediating emotional processing. Few studies have used direct electrical stimulation of the amygdala in humans to examine stimulation-elicited physiological and emotional responses, and the nature of such effects remains unclear. Determining the effects of electrical stimulation of the amygdala has important theoretical implications for current discrete and dimensional neurobiological theories of emotion, which differ substantially in their predictions about the emotional effects of such stimulation. To examine the effects of amygdala stimulation on physiological and subjective emotional responses we examined epilepsy patients undergoing intracranial EEG monitoring in which depth electrodes were implanted unilaterally or bilaterally in the amygdala. Nine subjects underwent both sham and acute monopolar electrical stimulation at various parameters in electrode contacts located in amygdala and within lateral temporal cortex control locations. Stimulation was applied at either 50 Hz or 130 Hz, while amplitudes were increased stepwise from 1 to 12 V, with subjects blinded to stimulation condition. Electrodermal activity (EDA), heart rate (HR), and respiratory rate (RR) were simultaneously recorded and subjective emotional response was probed after each stimulation period. Amygdala stimulation (but not lateral control or sham stimulation) elicited immediate and substantial dose-dependent increases in EDA and decelerations of HR, generally without affecting RR. Stimulation elicited subjective emotional responses only rarely, and did not elicit clinical seizures in any subject. These physiological results parallel stimulation findings with animals and are consistent with orienting/defensive responses observed with aversive visual stimuli in humans. In summary, these findings suggest that acute amygdala stimulation in humans can be safe and can reliably elicit changes in emotion physiology without significantly affecting subjective emotional experience, providing a useful approach for investigation of amygdala-mediated modulatory effects on cognition. Highlights: Increasing amplitudes of amygdala stimulation elicited dose-dependent increases in EDA and decreases in heart rate. In one patient, amygdala stimulation caused subjective experiences of fear and anxiety, accompanied by increased heart rate. Amygdala stimulation reliably elicits changes in autonomic activity in a dose-dependent and safe manner. At the amplitudes of stimulation delivered, amygdala stimulation elicits subjective emotional experiences only infrequently.